Peatlands and global warming: a study with special reference to South-East Asian countries - Ansari, Abdul Haseeb (INSI Publications, 2011)
All kinds of Peatlands have innumerable environmental and social functions. They are considered as an ideal habitat for plant and animal species. Conservation of peatlands means conservation of that class of biodiversity. This role gets significant in peatforests. Peatlands regulate water cycle as they have about 90 per cent water in them which regularly supplies good quality water to underground water channels. Peatforest absorb carbon dioxide (CO2) via photosynthesis. All kinds of peatlands, in totality, are considered as a very large carbon mass. Thus, from peatlands environment is protected and inhabitants get livelihood. When they decompose or get drained, they release a large quantity of CO2. If they are not properly managed, they release CH4 along with CO2 which cause global warming. The problem which the world right now is facing is that the total areas of peatlands are fast reducing for various reasons, e.g. mismanagement, facilitating agriculture, urbanization, growing oil palm plantations, and producing biomass energy. It is said that in South-East Asian countries, especially in Indonesia, peatlands are being drained and cleared for facilitating oil palm plantations. This is happening in spite of the fact that ASEAN countries of South-East Asia are members of the Ramsar Convention that aims at conservation of wetlands. There are legislations of the Member States, but it is said that their enforcement is poor. On the basis of facts, the paper evaluates these claims and offers suggestions for improving the conditions of this fragile ecosystem.